Phase I open-label study of afatinib plus vinorelbine in patients with solid tumours overexpressing EGFR and/or HER2 - Bahleda, Rastislav (Br J Cancer, 2018)
BACKGROUND: This phase Ib study evaluated afatinib plus vinorelbine in patients with advanced solid tumours overexpressing epidermal growth factor receptor (EGFR) and/or human EGFR 2 (HER2). METHODS: Maximum tolerated doses (MTDs) were determined for afatinib (20, 40 or 50 mg, once daily) combined with standard intravenous vinorelbine (part A; 25 mg m(−2) per week) or oral vinorelbine (part B; 60 mg m(−2) per week, increased to 80 mg m(−2) per week at week 3). Secondary end points for expanded MTD cohorts included assessments of safety, pharmacokinetics, tumour response and progression-free survival (PFS). RESULTS: The afatinib MTD was 40 mg with intravenous (MTD(A)) and oral (MTD(B)) vinorelbine. The most frequent cycle 1 dose-limiting toxicities were febrile neutropenia and diarrhoea, consistent with individual safety profiles of vinorelbine and afatinib. Common treatment-related adverse events included: diarrhoea (92.7%), asthenia (76.4%), nausea (63.6%), neutropenia (56.4%) and vomiting (54.5%). No notable pharmacokinetic interactions were observed. Best overall tumour response was stable disease in part A (16 out of 28 patients), and partial response in part B (3 out of 27 patients). Median PFS was 14.6 and 15.9 weeks for patients treated at the MTD(A) and MTD(B), including dose-escalation and expansion cohorts. CONCLUSIONS: Afatinib in combination with intravenous or oral vinorelbine demonstrated a manageable safety profile and antitumour activity at the MTD of 40 mg per day.